Polarimetric ApRES data on a profile across Dome C, East Antarctica, 2013-2014 - Corr, Hugh; Ritz, Catherine; Martin, Carlos (NERC EDS UK Polar Data Centre, 2021)
The radar data collected in 2013-2014 at Dome C, East Antarctica, aims to understand bulk preferred crystal orientation fabric near a dome. We measure changes in englacial birefringence and anisotropic scattering in 21 sites along a 36 km long profile across Dome C. These optical properties are obtained by analysing radar returns for different antenna orientations. More details can be found in Ershadi et al, 2021. Funding was provided by BAS National Capability and IPEV core funding. : The optical properties of the englacial ice at each site where obtained by comparing the return with four orthogonal antenna orientations. If we define H as the direction perpendicular to the East-West profile described by the sites, and V the parallel direction to the profile; and we label each of the measurements with the two orientations of the transmitting and receiving antennas; the four orthogonal antenna orientations are HH,HV,VH and VV. The spatial resolution is determined by the location of the sites, 21 in a 36 km profile. The distance between sites is closer near Dome C, about 500 m, than farther away, 3 km or so. The vertical resolution depends on the quality of the radar return but it is related to the wavelength of the signal on ice, about 0.4 m. : Radar: ApRES (British Antarctic Survey's Autonomous phase-sensitive Radio-Echo Sounder) - chirps of 200 to 400 MHz in time intervals of 1 s, with 8 m between antennas. Model RMB1B SN012. (More details in the file headers.) : The quality of the data is similar in all the sites. It varies mainly with depth: In the top 2000 m the return is consistently above the noise level. Below 2000 m, the return signal is weak, apart from some isolated reflectors, up to the bedrock that is clear in all the records. The parallel antenna configuration measurements, HH and VV, have larger signal-to-noise ratio, than the perpendicular ones, HV and VH. This is because of experimental design as system configuration is identical in all the antenna orientations.